2017
DOI: 10.1038/nsmb.3444
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of TIR-domain-assembly formation in MAL- and MyD88-dependent TLR4 signaling

Abstract: Toll-like receptor (TLR) signaling is a key innate immunity response to pathogens. Recruitment of signaling adapters such as MAL (TIRAP) and MyD88 to the TLRs requires Toll/interleukin-1 receptor (TIR)-domain interactions, which remain structurally elusive. Here we show that MAL TIR domains spontaneously and reversibly form filaments in vitro. They also form cofilaments with TLR4 TIR domains and induce formation of MyD88 assemblies. A 7-Å-resolution cryo-EM structure reveals a stable MAL protofilament consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
227
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(240 citation statements)
references
References 75 publications
12
227
0
1
Order By: Relevance
“…This behaviour was consistent no matter what concentrations of the protein were expressed ( Figure 1B). The absence of large events is consistent with the findings by Ve et al that MyD88 TIR alone does not spontaneously polymerise 12 . Similarly, comparisons of the brightness profiles, PCH and FCS and purified GFP-foldon data obtained when the MyD88 DD alone is expressed, demonstrates that it too consistently forms small oligomers, more specifically octamers based on PCH analysis (Figure 2A-C).…”
Section: At Low Concentrations Both the Tir And Death Domains Are Resupporting
confidence: 92%
See 2 more Smart Citations
“…This behaviour was consistent no matter what concentrations of the protein were expressed ( Figure 1B). The absence of large events is consistent with the findings by Ve et al that MyD88 TIR alone does not spontaneously polymerise 12 . Similarly, comparisons of the brightness profiles, PCH and FCS and purified GFP-foldon data obtained when the MyD88 DD alone is expressed, demonstrates that it too consistently forms small oligomers, more specifically octamers based on PCH analysis (Figure 2A-C).…”
Section: At Low Concentrations Both the Tir And Death Domains Are Resupporting
confidence: 92%
“…For many years, TIR domain associations, which are weak and transient, have been seen to contribute little to the oligomerisation status of signalling proteins 27,28 . However, the recent cryoEM structure of Mal TIR domain in filamentous form, as well as novel studies 12 ,demonstrated that upon specific ligand binding TIR-containing proteins cooperatively assemble into large multiprotein complexes 12,23 . The TIR domain of MyD88 was also demonstrated to polymerise but only upon seeding by Mal filaments.…”
Section: Full-length Myd88 Biophysical Behaviour and Its Link To Signmentioning
confidence: 99%
See 1 more Smart Citation
“…TIR domains function as a homotypic interaction motif, and the molecular basis of interactions has recently been characterized for TLR4 signalling assembly with MyD88 and MAL (Ve et al, 2017). The TIR domains from the mammalian protein SARM1 and some bacterial proteins have also been shown to have NAD + -cleavage activity (Essuman et al, 2017(Essuman et al, , 2018; this finding suggests there may be evolutionary, rather than merely structural links with bacterial enzymes such as the CMP hydrolase MilB.…”
Section: Secondary Structure-based Phylogenetic Inferencementioning
confidence: 99%
“…3). In fact, several structures of the TLR4/Adaptor/LPS complex and the TIR domain have been resolved separately (e.g., PDB codes: 3FXI [15] and 5UZB [16], respectively). Furthermore, the structure of the TLR4 transmembrane domain was recently solved by nuclear magnetic resonance (PDB code: 5NAM [17]) completing the atomistic modular description of the entire receptor.…”
Section: Lipid-stimulated Prrs (Tlr4)mentioning
confidence: 99%